Biomimetic Peptide Nanowires Designed for Conductivity - Bernard Mostert (ACS Omega, 2019)
The filamentous peptide-based nanowires produced by some dissimilatory metal-reducing bacteria, such as Geobacter sulfurreducens, display excellent natural conductivity. Their mechanism of conduction is assumed to be a combination of delocalized electrons through closely aligned aromatic amino acids and hopping/charge transfer. The proteins that form these microbial nanowires are structured from a coiled-coil, for which the design rules have been reported in the literature. Furthermore, at least one biomimetic system using related synthetic peptides has shown that the incorporation of aromatic residues can be used to enhance conductivity of peptide fibers. Herein, the de novo design of peptide sequences is used to enhance the conductivity of peptide gels, as inspired by microbial nanowires. A critical factor hampering investigations in both microbiology and materials development is inconsistent reporting of biomaterial conductivity measurements, with consistent methodologies needed for such investigations. We have reported a method herein to analyze non-Ohmic behavior using existing parameters, which is a statistically insightful approach for detecting small changes in biologically based samples. Aromatic residues were found to contribute to peptide gel conductivity, with the importance of the peptide confirmation and fibril assembly demonstrated both experimentally and computationally. This is a small step (in combination with parallel research under way by other researchers) toward developing effective peptide-based conducting nanowires, opening the door to the use of electronics in water and physiological environments for bioelectronic and bioenergy applications.